Impact of diwali firecrackers on air quality in India and its effect on the health - SONIA SINGLA; MINU KESHERI; SWARNA KANCHAN; AJAY MISHRA (International Journal of Pharma and Bio Sciences, 2019)
Air contamination happens when unreasonable amount of substances including gases, particulates, and organic atoms enter earth’s environment. It might cause maladies, hypersensitivities and even demise of people. Air Pollution is worst in India and is likely to result in more deaths. The top five causes of deaths worldwide are CVD, COPD, lower respiratory infections, and lung cancer. The objective of the paper is to highlight the air pollutants in India and their effects on health. As Delhi is the capital of India, so the focus of research was more on Delhi and Haryana from 2012 to 2018.